Analysis and comparison of fast multiplier circuits based on different parameters - Aaron D’costa, Mr; Abdul Razak, Dr; Shazia Hasan, Dr (International Journal of Engineering and Technology, 2018)
Digital multiplier circuits are used in computers. A multiplier is an electronic circuit used in digital electronics to multiply two binary numbers. Multiplier circuits are used in ALU for binary multiplication of signed and unsigned numbers. The delay, area and power consumption are the 3 most important design specifications a chip designer has to consider. Delay of the circuit is directly proportional to the delay of a multiplier. Increased delay in the multiplier leads to higher delay in the circuit. Therefore research is carried out as to how to reduce the delay of the multiplier block so as to reduce the delay of whole circuit. The main purpose is to deal with high speed and lower power consumption even after decreasing the silicon area. This makes them well-suited for numerous complex and convenient VLSI circuit implementations. The fact however, remains that area and speed are two contradictory performance restrictions. Hence, increase in speed always results in the use of more and complex hardware. Different arithmetic techniques can be used to implement different multiplier circuits. The focus of this paper is to implement various multiplier circuit and compare them. The timing signals can be observed using software such as Modelsim and Xilinx.Â Â